A Sardinien boundary dispute and agriculture - Takács, Levente (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In AD 69 the proconsul Helvius Agrippa had to settle a boundary dispute between two small Sardinian communities. One of them, the Galillenses, were permitted to produce the tablet pertaining to the matter from the imperial archive. The inscription fails to mention if the Galillenses had taken any action to get the tabula from Rome. Specialist literature does not give any viable explanation for this absence. The conclusion may thus be drawn that the reason for the Galillenses’ attempt to delay ‘handing over’ pertains to the anticipated yield of some kind of investment they had made. The article tries to prove that the Galillenses attempted postponing the deadline with the aim of saving crops awaiting harvest.